Combined Exp-Function Ansatz Method and Applications. (6th June 2013) - Mu, Gui; Liu, Jun; Dai, Zhengde; Liu, Xi
Abstract : Our aim is to present a combined Exp-function ansatz method. This method replaces the traditional assumptions of multisolitons by a combination of the hyperbolic functions and triangle functions in Hirota bilinear forms of nonlinear evolution equation. Using this method, we can obtain many new type analytical solutions of various nonlinear evolution equations including multisoliton solutions as well as breath-like solitons solutions. These solutions will exhibit interesting dynamic diversity.